Virtual Lab for Thresholded Image Difference - Montenegro Joo, Javier (2011)
An educational Virtual Lab, a software oriented to teaching and learning, applied to the study of the Thresholded Difference of grey-leveled images has been developed. This intuitively-easy-to-use Virtual Lab allows studying the threshold-controlled difference of two input images. Interesting results emerge when detecting the thresholded difference of pairs of images, like the effect appearing in the case of image subtraction of two completely different images, an effect setting up the basis for Controlled Image Fusion. Image difference algorithms belong to Digital Image Processing, a computer tool with every time more applications in science and in engineering.